Trans-cultural expressions of self-concept/self-esteem and personality development/character building values as predisposing variables of sports participation among adolescents in Nigeria and Togo (2017)
This study examined the trans-cultural expressions of self-concept/self-esteem and personality development/character building values as predisposing variables of sports participation among adolescents in Nigeria and Togo. For the purpose of the study, two research hypotheses were generated and tested. The descriptive survey design, multi-stage sampling technique and self-developed four-point Likert type questionnaire were used. A reliability coefficient of .89, was obtained through the use of Crombach alpha. The findings revealed that adolescents in the two countries expressed self-concept/self-esteem and personality development/character building values as predisposing variables of sports participation. Consequently, it was therefore, recommended that; sports competitions should be organized regularly as adolescents enjoy competitions and thus, could be motivated to participate in sports through it. Sports Services providers should endeavor to find means of organising enlightenment programmes on the benefits inherent from sports participation, through this, many adolescents who do not know the benefits of sports participation will be informed and consequently get involved in it. Public and private schools administrators should establish functional and well-supervised sports units in their schools. Private individuals should assist the government in promoting sports by sponsoring sports programmes, awarding scholarships to excellent sports participants. Parents should encourage their children/wards to participate in sports by providing assistance in form of money, equipment among others to them, on order to stimulate, sustain their interest and facilitate their participation in sports